Exploring the use of lesson study to enhance students' conceptual understanding in science subjects in a public school in Lagos State - Abidoye, Aderonke Ibiyemi (2015)
The purpose of this research was to investigate how the use of lesson study will enhance students’ conceptual understanding in Physics, Chemistry and Biology; to examine how lesson study will develop the critical thinking and problem-solving skills in students; to determine the extent to which participation in lesson study group will develop the instructional ability of teachers to teach for conceptual understanding and to investigate how lesson study will foster collaboration among the science teachers to teach for conceptual understanding. A qualitative case study approach through an action research design was the methodology employed for the study. Three secondary school teachers, Vice Principal (Academics) of the school, an expert invited from outside and thirty-nine science students in Senior Secondary School 2 (SSS 2) from a public school participated in the study. The instruments used to collect the data were: observation notes, semi-structured interview, teacher-made conceptual tests in Physics, Chemistry and Biology, research lesson feedback form and lesson study feedback survey. Analysis of the data revealed that lesson study enhanced students’ conceptual understanding in Chemistry and Biology than in Physics. Evidence indicated that lesson study approach developed the students’ critical and problem-solving skills. The study also revealed that lesson study approach developed the instructional ability of the teachers that took part in lesson study process to teach for conceptual understanding and it fostered collaboration among the science teachers. This study concluded that every teacher who wants the best for his/her students should not hesitate to join teams that will implement effective, creative and innovative teaching approaches such as lesson study in order to develop students’ conceptual understanding in all the subjects and improve their performance in every standardized examination. Recommendation for future research was made to extend lesson study approach to all the teachers’ classrooms in the school in order to improve students’ learning in other subjects.